PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Satuan Kerja Perangkat Daerah Di Kabupaten Kendal) - Niken Isandiyana, 13.05.52.0012; Srimindari, Ceacilia (Students Journal of Accounting and Banking, 2017)
This study examined the influence of Quality of Human Resources and Utilization of Information Technology on the Quality of Local Government Finance Report. This research was conducted at the Regional Work Units in Kendal.Â The sampling method using random sampling. Relationships between variables or effect described by using multiple regression analysi. The results showed that the quality of Human Resource Quality positive and significant impact on Quality Local Government Finance Report, Utilization of Information Technology positive and significant impact on Quality Financial Statements of Local Government. The suggestions for the this research is the area of financial management, especially accounting department was able to perform the duties and functions of accounting in accordance with the legislation in force, so that the quality of financial reporting can be better, as well as improving the quality of human resource and utilization of information technology by providing training and motivation.Keywords: Quality of Human Resources, Technology Utilization, and Quality Government Local Government Finance Report